2016
DOI: 10.3390/su8121321
|View full text |Cite
|
Sign up to set email alerts
|

Wave Climate Resource Analysis Based on a Revised Gamma Spectrum for Wave Energy Conversion Technology

Abstract: Abstract:In order to correctly predict and evaluate the response of wave energy converters (WECs), an accurate representation of wave climate resource is crucial. This paper gives an overview of wave resource modeling techniques and applies a methodology to estimate the naturally available and technically recoverable resource in a given deployment site. The methodology was initially developed by the Electric Power Research Institute (EPRI), which uses a modified gamma spectrum to interpret sea state hindcast p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…The measurements have a 6-h time step (00-06-12-18 UTC): In order to identify the wave variations in the offshore areas, two reference points (OP1 and OP2) were defined in the western and eastern parts of the sea, respectively. Besides the climatological investigations, the information provided by the nearshore points can be considered relevant for activities related to coastal engineering works or renewable projects, while the offshore points may hold interest for marine navigation and sea safety [28,29]. Most of the research effort is focused on the Black Sea basin, while the conditions from the Azov Sea are less discussed.…”
Section: The Target Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements have a 6-h time step (00-06-12-18 UTC): In order to identify the wave variations in the offshore areas, two reference points (OP1 and OP2) were defined in the western and eastern parts of the sea, respectively. Besides the climatological investigations, the information provided by the nearshore points can be considered relevant for activities related to coastal engineering works or renewable projects, while the offshore points may hold interest for marine navigation and sea safety [28,29]. Most of the research effort is focused on the Black Sea basin, while the conditions from the Azov Sea are less discussed.…”
Section: The Target Areasmentioning
confidence: 99%
“…Besides the climatological investigations, the information provided by the nearshore points can be considered relevant for activities related to coastal engineering works or renewable projects, while the offshore points may hold interest for marine navigation and sea safety [28,29]. Most of the research effort is focused on the Black Sea basin, while the conditions from the Azov Sea are less discussed.…”
Section: The Ecmwf Datasetmentioning
confidence: 99%
“…The importance of understanding the most common spectral shapes at a potential WEC site have been illustrated by [8], who showed that they can directly affect the degree of wave shadowing predicted (if frequency dependent modelling is applied), especially in the presence of bimodal spectra. Recent work by [35][36][37] has sought to further characterise wave spectra at a given location for the purposes of wave energy resource assessment, including during bimodal wave conditions. Previous WEC modelling at Wave Hub [6] was critiqued [27] for applying default wave directional spreading values that were not representative of the site under study, or of wave conditions of interest to surfers.…”
Section: Effects Of Wave Energy Extraction On Wave Climatementioning
confidence: 99%
“…Much work, both theoretical [13][14][15][16] and experimental [17][18][19], has been accomplished to maximize the power absorption and increase the force in the connection line for this type of WEC. An optimal WEC with high power output and high survivability will have high mean forces and low peak forces.…”
Section: Introductionmentioning
confidence: 99%